Faktor-Faktor yang Mempengaruhi Praktik Perataan Laba Di Perbankan - Maulana, Al Adiyat (Journal of Accounting and Investment, 2014)
The research was conducted to determine firm size , auditor reputation, institusional ownership, and financial leverage  on the practice of income smoothing in financial companies banking industries listed on the Indonesia Stock Exchange (IDX). The sample in this study were financial companies listed on the Indonesia Stock Exchange (IDX) during the years 2009-2013. Data were collected through purposive sampling. The analysis is carried out multiple linear regression and t tests with the first test of classical assumptions. Through multiple linear regression analysis is known that the variable profitabilitas has a significant influence on the practice of income smoothing. This is indicated by regresional relationship between the dependent variable with several independent variables and a significance value smaller than 0.05. While the firm size variable, auditor reputation, institusional ownership, and financial leverage do not have effect on the practice of income smoothing because it has a significance value greater than 0.05.